Attitudes of undergraduate medical students toward mental illnesses and psychiatry - Nimisha D Desai; Paragkumar D Chavda (Wolters Kluwer Medknow Publications, 2018)
Background: Worldwide, studies show negative attitude among medical students toward psychiatry and mental illness. The knowledge of the attitude and awareness of the undergraduate medical students toward psychiatry, mental health, and psychiatric disorders are most important as they are going to be involved in the care of these patients either directly or indirectly during the later years of their careers. Aim: This study aims to assess attitude toward psychiatry and mental illness among undergraduate medical students. Methodology: The responses of 67 medical students from the 6th semester (third professional year) batch who completed their 2-week clinical posting of psychiatry in 4th semester (i.e., second professional year) were collected using validated questionnaires, attitude towards mental illness (AMI), and attitude towards psychiatry (ATP) that assessed their attitudes to psychiatry and mental illness. Double data entry and validation were done using EpiData and analysis using Epi Info software. Results: Median AMI score was 54 (out of maximum 100) showing a neutral AMI. Median ATP score was 82 (out of maximum 150) also showing a neutral ATP. The theme-wise analysis showed that the attitude of students toward psychiatrist and psychiatry branch was relatively better compared to their AMI. Conclusion: Undergraduate students have a neutral attitude to psychiatry and mental illness. More efforts are needed to change the attitude to favorable side.